2005
DOI: 10.1177/112067210501500117
|View full text |Cite
|
Sign up to set email alerts
|

Macula off Retinal Detachments. how Long Can They Wait before it is Too Late

Abstract: The best mean postoperative vision (LogMAR 0.35) was seen in patients with detachment of <1 week duration. Patients <60 years are more likely to achieve visual improvement despite the duration of the detachment. Macula off detachments of >6 weeks duration have a significantly poor postoperative visual prognosis. Awareness of this visual prognosis can assist in planning the timing of surgery to ensure an acceptable result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 25 publications
0
21
1
2
Order By: Relevance
“…Although other factors were discussed in previous studies, we could not confirm the relevance of duration of macular detachment (as it was not recorded in the SPR Study) [6,23,25,26] and patient age [6,23,25,29] to final visual results.…”
Section: Intraoperative Laser Usecontrasting
confidence: 74%
“…Although other factors were discussed in previous studies, we could not confirm the relevance of duration of macular detachment (as it was not recorded in the SPR Study) [6,23,25,26] and patient age [6,23,25,29] to final visual results.…”
Section: Intraoperative Laser Usecontrasting
confidence: 74%
“…These include the age of patients,12 21 22 preoperative PVR,8 18 20 extension of RD,8 11 previous RD or other ocular surgery,18 and the status of the macula 12 20 22. In our series, only 35% of the RDs had macula-on at the time of surgery.…”
Section: Discussionmentioning
confidence: 62%
“…[11][12][13][14][15][16]21 In addition, two reviews were found. The 14 studies found consisted of 7 prospective observational 9,10,16,18-20,22 and 7 retrospective observational studies.…”
Section: Systematic Reviewmentioning
confidence: 99%